ANALYSIS OF E-RAPORT IMPLEMENTATION ACCEPTANCE IN IMPROVING THE QUALITY OF ELEMENTARY SCHOOL EDUCATION USING THE TECHNOLOGY ACCEPTANCE MODEL APPROACH - Wahyu Febriana; Subandi Subandi (Jurnal TAM (Technology Acceptance Model), 2026)
This study aims to analyze the acceptance of E-Raport system implementation in improving the quality of elementary education in Pringsewu Regency using the Technology Acceptance Model approach. The research employed a quantitative method with a survey design involving 56 respondents, consisting of 22 school operators and 34 elementary school teachers. Data were collected using a Likert-scale questionnaire measuring Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BI). Data analysis was conducted using SEM-PLS to examine the relationships among variables. The results indicate that all variables fall into high categories, with mean values above 4.00. Hypothesis testing reveals that PEOU significantly influences PU, while both PEOU and PU significantly affect ATU. Furthermore, ATU has the strongest influence on BI. The R-square value of 0.66 indicates that the model explains 66% of the variance in behavioral intention to use E-Raport. These findings suggest that ease of use and perceived usefulness are key determinants in shaping user attitudes and intentions toward technology adoption. The study highlights the importance of developing user-friendly systems and enhancing user competencies to optimize E-Raport implementation in improving the quality of elementary education.